Ryan Gander: Culturefield - Burns, Aileen; Gander, Ryan; Lundh, Johan; Marston, Rebecca May (Verlag der Buchhandlung Walther Konig, Koln; Koenig Books, London, 2014)
Published on the occasion of the exhibition Make Every Show Like It's Your Last. The meticulously researched projects of British artist Ryan Gander (born 1976), realized in a gamut of media, have included such conceptual gestures as an invented word, a chess set, a television script and a children's book. This substantial volume surveys his diverse oeuvre.
English; French
Keywords: N4390-5098 Visual Arts. Exhibitions